KOMPYUTER TEXNOLOGIYALARÍ JÁRDEMINDE XIMIYA PÁNINIŃ TIYKARǴÍ TÚSINIKLERI - Jumamuratov, R.E.; Kaipbergenov, A.T. (SCIENCE and SOCIETY, 2019)
The article is devoted to the use of computer technology in chemistry teaching. The article presents the numerous works of chemists devoted to the computerization of a chemical experiment, for solving problems and conducting quantitative calculations, for the formation of generalized chemistry skills based on the algorithmization and computerization of training.